1984
DOI: 10.1038/309261a0
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependent block by Mg2+ of NMDA responses in spinal cord neurones

Abstract: Acidic amino acids are putative excitatory synaptic transmitters, the ionic mechanism of which is not well understood. Recent studies with selective agonists and antagonists suggest that neurones of the mammalian central nervous system possess several different receptors for acidic amino acids, which in turn are coupled to separate conductance mechanisms. N-methyl-D-aspartic acid (NMDA) is a selective agonist for one of these receptors. The excitatory action of amino acids acting at NMDA receptors is remarkabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

43
1,283
4
16

Year Published

1991
1991
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,651 publications
(1,361 citation statements)
references
References 14 publications
43
1,283
4
16
Order By: Relevance
“…It has been demonstrated that Mg 2 + binds to a site within the NMDA-gated ionophore (Nowak et al , 1984). The blocking of the NMDA receptor-associated channel by Mg 2 + is strongly voltage dependent (Mayer et al , 1984). However, the persistent phase of depolarization in duced by ischemic conditions in rat hippocampal slices is selectively blocked by lowering calcium and raising magnesium as well as by NMDA antag onists.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that Mg 2 + binds to a site within the NMDA-gated ionophore (Nowak et al , 1984). The blocking of the NMDA receptor-associated channel by Mg 2 + is strongly voltage dependent (Mayer et al , 1984). However, the persistent phase of depolarization in duced by ischemic conditions in rat hippocampal slices is selectively blocked by lowering calcium and raising magnesium as well as by NMDA antag onists.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis of Parsons et al (1993) was made on the basis of the fact that NMDA receptors are activated physiologically by mM concentrations of synaptically-released glutamate which transiently strongly depolarize the postsynaptic membrane (Clements et al, 1992;Pongracz et al, 1992) whereas, even during acute excitotoxic insults like ischaemia, relatively low pM concentrations of interstitial glutamate cause only moderate membrane depolarization but for much longer periods of time (Benveniste et al, 1984;Globus et al, 1989;1991;Andine et al, 1991;Buisson et al, 1992;Mitani et al, 1992;Hashimoto et al, 1994). It is well accepted that the strong voltage-dependency and rapid unblocking kinetics of Mg2" (Nowak et al, 1984;Mayer et al, 1984) allow this cation to leave the NMDA receptor channel upon transient physiological activation during the induction of LTP. Indeed, precisely these properties make the NMDA receptor channel complex inherently suited for its role in mediating synaptic plasticity (Herron et al, 1986;Bliss & Collingridge, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The NMDAR is a ligand-gated neuronal ion channel, which, at resting membrane potentials, is blocked by Mg 2+ (Mayer et al, 1984). Channel opening occurs through binding of the coagonists, glutamate (or NMDA) and glycine (Jahr and Stevens, 1987;Johnson and Ascher, 1987).…”
Section: Introductionmentioning
confidence: 99%